The inclusiveness of community participation in village development planning in Indonesia. Issue 5 (3rd July 2020) - Damayanti, RatnaAyu; Syarifuddin, Syarifuddin
ABSTRACT: This article aims to reveal the inclusiveness of community participation in village development planning in Indonesia. Using participatory rural appraisal, the study found that development planning deliberation forums have yet to involve the community inclusively in village planning. The community is only represented by village leaders who are generally closely aligned with the government. Moreover, participatory planning does not involve the community continuously in the development process. Therefore, rural development processes in Indonesia do not yet translate and address community needs.